2016
DOI: 10.1186/s40550-016-0028-4
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organochlorine pesticide residues in cocoa beans from Ghana, a concern for public health

Abstract: Background: Residual levels of fifteen (15) organochlorine pesticides were determined in 32 cocoa bean samples collected from sixteen (16) selected cocoa farms in the Dormaa West District of Ghana to assess the levels of pesticides contamination. Results:The results show that all cocoa bean samples analysed from the study area had one or more organochlorine pesticide residues detected in them. The study revealed the presence of eight organochlorine pesticide residues in the cocoa bean samples analysed at varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Presence of BHCs has been reported in Nigeria cocoa farms [9,19],which suggests the previous use of technical BHC in Nigerian cocoa production. The results of lindane in this study were within the levels reported by Frimpong et al [20] and Okoffo et al [21], while Oyekunle et al [16] showed higher levels. The measured concentrations of lindane were far below the European Union (EU) Maximum Residue Limits (MRLs) of 1.0 mg/kg.…”
Section: Resultssupporting
confidence: 89%
“…Presence of BHCs has been reported in Nigeria cocoa farms [9,19],which suggests the previous use of technical BHC in Nigerian cocoa production. The results of lindane in this study were within the levels reported by Frimpong et al [20] and Okoffo et al [21], while Oyekunle et al [16] showed higher levels. The measured concentrations of lindane were far below the European Union (EU) Maximum Residue Limits (MRLs) of 1.0 mg/kg.…”
Section: Resultssupporting
confidence: 89%
“…Predominant pesticides used in the area are endosulfan and chlorpyrifos which are supervised and regulated by the irrigation authorities (Ntow 2008). Some farmers also obtain cheap but effective pesticides from neighboring countries such as Togo and Burkina Faso which are not approved by the by EPA, Ghana, the pesticides regulating authority (Okoffo et al 2016). The dam has a maximum storage capacity of about 5.0 × 10 5 m 3 (Pelig-Ba 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Considering Mexico, Pérez et al (2013) showed that even though several harmful pesticides have been banned, while some are authorized for use despite being prohibited in many countries. There are reports of a number of obsolete products in use or being stored inappropriately that pose risks to the environment further of inadequate regulation and management, trade, weak enforcement of bans on pesticides importation, illegal use/application and lack of logistics to monitor these pesticides (Okoffo et al, 2016). The presence of pesticide residues in vegetables and fruits is frequent, being reported in over 50% of the samples tested in national monitoring and in products exported to the United States in specific studies.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of organochlorine pesticides in agricultural crops and processed foods also indicates the need for improving residue control at production, tighter regulation of pesticide spraying, and also tighter regulation in the sale of pesticides, as well as for education of farmers and the implementation of integrate pest management methods. Nevertheless, monitoring programs are increasingly important and essential to ensure minimal pesticide residue levels in food (Narayan et al 2012;Wang et al, 2013;Okoffo et al, 2016).…”
Section: Resultsmentioning
confidence: 99%